Lower Pliensbachian caldera volcanism in high-obliquity rift systems in the western North Patagonian Massif, Argentina - Benedini, Leonardo (2014)
In the Cerro Carro Quebrado and Cerro Catri Cura area, located at the border between the Neuquén Basin and the North Patagonian Massif, the Garamilla Formation is composed of four volcanic stages: 1) andesitic lava-flows related to the beginning of the volcanic system; 2) basal massive lithic breccias that represent the caldera collapse; 3) voluminous, coarse-crystal rich massive lava-like ignimbrites related to multiple, steady eruptions that represent the principal infill of the system; and, finally 4) domes, dykes, lava flows, and lava domes of rhyolitic composition indicative of a post-collapse stage. The analysis of the regional and local structures, as well as, the architectures of the volcanic facies, indicates the existence of a highly oblique rift, with its principal extensional strain in an NNE–SSW direction (∼N10°). The analyzed rocks are mainly high-potassium dacites and rhyolites with trace and RE elements contents of an intraplate signature. The age of these rocks (189 ± 0.76 Ma) agree well with other volcanic sequences of the western North Patagonian Massif, as well as, the Neuquén Basin, indicating that Pliensbachian magmatism was widespread in both regions. The age is also coincident with phase 1 of volcanism of the eastern North Patagonia Massif (188–178 Ma) represented by ignimbrites, domes, and pyroclastic rocks of the Marifil Complex, related to intraplate magmatism.